(untitled) (Bangladesh Heart Journal, 2024)
Introduction : Diabetes mellitus, especially Type 2, is a common metabolic problem in Bangladesh with serious complications like diabetic foot ulcer. The relationship between HbA1c, serum magnesium, and lipid profile in type 2 DFU patients was examined in this study. Aim of the study: The aim of this study was to examine the correlation between HbA1c, serum Magnesium, and lipid profile in type 2 diabetic foot ulcer and without foot ulcer patients. Methods: This cross-sectional study was conducted in the Department of Biochemistry and Molecular Biology, BIRDEM Academy, Dhaka, Bangladesh during the period from January 2018 to December 2018 Result: In total 120 respondents who were adult male and female were included in the study. In our study, we found that the majority of our patients (58.3%) were aged between 41-50 yrs. in group II. We found the percentage of male and female participants were 66.7% and 33.3% in group I and 51.7% and 48.3% in group II respectively. The negative correlation was found between serum magnesium with fasting plasma glucose and Triacylglycerol in group I. The significant positive correlation was found between serum Mg and HDL-c (r=0.443; p<0.01) in group I. Conclusion: Diabetes Mellitus, notably Type 2, poses challenges in Bangladesh, including Diabetic Foot Ulcer (DFU). This study explores links between HbA1c, serum magnesium, and lipid profile in Type 2 DFU patients, potentially guiding early interventions and improving diabetic care outcomes. Bangladesh Heart Journal 2024; 39(1): 24-30